Acne in late adolescence and risk of prostate cancer. Issue 8 (14th December 2017) - Ugge, Henrik; Udumyan, Ruzan; Carlsson, Jessica; Andrén, Ove; Montgomery, Scott; Davidsson, Sabina; Fall, Katja
Abstract : Accumulating evidence suggest that Propionibacterium acnes may play a role in prostate carcinogenesis, but data are so far limited and inconclusive. The aim of this population‐based cohort study was therefore to test whether presence of acne vulgaris during late adolescence is associated with an increased risk of prostate cancer later in life. We identified a large cohort of young men born in Sweden between 1952 and 1956, who underwent mandatory assessment for military conscription around the age of 18 ( n = 243, 187). Test information along with health data including medical diagnoses at time of conscription was available through the Swedish Military Conscription Register and the National Patient Register. The cohort was followed through linkages to the Swedish Cancer Register to identify the occurrence of prostate cancer until December 31, 2009. We used Cox regression to calculate adjusted hazard ratios (HR) and 95% confidence intervals (95% CI) for the association between acne in adolescence and prostate cancer risk. A total of 1, 633 men were diagnosed with prostate cancer during a median follow‐up of 36.7 years. A diagnosis of acne was associated with a statistically significant increased risk for prostate cancer (adjusted HR: 1.43 95%; CI: 1.06–1.92), particularly for advanced stage disease (HR: 2.37 95%; CI 1.19–4.73). A diagnosis of acne classified as severe conferred a sixfold increased risk of prostate cancer (HR: 5.70 95% CI 1.42–22.85). Data from this large prospective population‐based cohort add new evidence supporting a role of P. acnes infection in prostate cancer. Abstract : What's new? Some evidence has suggested that acne vulgaris may increase the risk of prostate cancer, but the data have been inconsistent. The results of this prospective cohort study support a link between acne in adolescence and prostate cancer later in life, potentially implicating the bacteria Propionibacterium acnes and resulting inflammation in prostate carcinogenesis. These results also suggest that the association may be stronger for the most severe type of acne and for advanced prostate cancer.